Pilar-Pilar Keluarga Sakinah Menurut Hadis Nabi saw. - M. Kasim; Muhammad Dhiyaul Haq (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This reseach aimed to examine the quality of hadith (hadith criticism from the side of sanad and matan) and understanding (syarah) of one of hadith of the Prophet related to the pillars of the sakinah (tranquil) family found in al-Kutub as-Sittah. This research employed descriptive qualitative method with the approach mawdu>'iy and tahli>liy. The results show that: (1) sanad of hadiths that were studied were hadiths that reach the sahih (valid) degree that could be accounted for their quality and credibility. All sanad of the hadith reach their narrator successively and in chain, muttasil, and there is no reprehensible narrator. Also in the hadith there are syawahid; (2) In terms of matan, although there are differences in the use of pronunciation or sentence forms and the addition of certain words in the editorial team, but subtantially this does not change the three pillars of the sakinah family in the world, namely good neighbors, comfortable vehicles, and a big house, as well as a complementary addition from a hadith that becomes a syahid is: having a rightous wife; (3) From the sub-theme of the sakinah family that was traced related to the pillars of the sakinah family, there were 5 hadiths; (4) The ideal concept of the sakinah family is an alternative solution to the various social problems that occur